KEPENTINGAN AMERIKA SERIKAT MEMBANTU UKRAINA DALAM KONFLIKNYA DENGAN RUSIA PADA TAHUN 2022-2023 - Sari, Ika Nadia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This thesis analyzes the "Interests of the United States in Assisting Ukraine in its Conflict with Russia in 2022-2023." The full-scale invasion carried out by Russia on February 24, 2022, against Ukraine caused Ukraine to struggle in defending its country. In this context, the United States implemented foreign policy to provide assistance and support to Ukraine through economic aid and military equipment, as well as imposing economic sanctions on Russia aimed at weakening Russia’s ability to wage war. The United States' support became the largest compared to other countries. This thesis is written using the Power Balance theory by Hans Joachim Morgenthau. The methodology used in this thesis is qualitative, with data collection techniques based on document analysis. The results of this paper indicate that the United States' provision of substantial assistance to Ukraine is an effort to counterbalance Russia’s influence and maintain the power balance in Eastern Europe. Keywords: Balance of Power, National Interest, International Conflict